2020
DOI: 10.1111/ap.12460
|View full text |Cite
|
Sign up to set email alerts
|

Future thinking is related to lower delay discounting than recent thinking, regardless of the magnitude of the reward, in individuals with schizotypy

Abstract: Objective People often prefer immediate small rewards compared to delayed larger rewards, which is referred to delay discounting. Schizotypy, a subclinical group at risk for schizophrenia, tends to discount more than healthy controls. Episodic future thinking (EFT), in which people mentally simulate future events to pre‐experience the future, has been found to reduce delay discounting in the general population, but whether this effect can be found in individuals with schizotypy remains unknown. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 67 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…The DD paradigm can be divided into two types: the fixed task in which the amount of reward is fixed, not influenced by participants’ choices, and the varied task in which the amount of reward changed according to participants’ responses. Both paradigms showed medium and similar sized effects of EFT on DD (Bromberg et al, 2017; Jia et al, 2020). These results suggested that the effect of EFT was stable across DD paradigms.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The DD paradigm can be divided into two types: the fixed task in which the amount of reward is fixed, not influenced by participants’ choices, and the varied task in which the amount of reward changed according to participants’ responses. Both paradigms showed medium and similar sized effects of EFT on DD (Bromberg et al, 2017; Jia et al, 2020). These results suggested that the effect of EFT was stable across DD paradigms.…”
Section: Discussionmentioning
confidence: 85%
“…This might be because a longer delay was associated with a higher DD. EFT could broaden the temporal window and shorten the subjective duration, and this effect was stronger during longer delays (Jia et al, 2020; Snider et al, 2016; Sze et al, 2017).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation